DEMOCRATIC REPUBLIC OF CONGO CRISIS: AN ASSESSMENT OF AFRICAN UNION’S PRINCIPLE OF NON-INDIFERENCE - Danfulani, John (European Scientific Journal, ESJ, 2015)
Democratic Republic of Congo (DRC) has a troubling history of civil wars since gaining political independence from Belgium in 1960. All DRC’s civil wars had external dimensions who got involved to either defend ideological client or protect economic or strategic interests. The 1998 unsuccessful attempt to oust President Laurent Kabila attracted two blocks of opposing multi-national forces into DRC. It was an instance of interference in internal affairs of DRC by neighbouring states and their allies. The status of pro-Kinsasha forces was clear in international law because they were invited by a legitimate government. While that of anti-Kinsasha group cannot be situated within the ambit of any international law hence making their presence in DRC at the time of the civil war illegitimate. Activities of anti-Kabila forces were not covered by AU’s July 2000 principle of nonindifference. Interference by foreign forces on the side of the rebel was a brazen act of aggression and flagrant disrespect for the territorial integrity of DRC. AU must act to safeguard abuse of the non-indifference clause by member states and stiffer sanctions imposed on belligerent actors. Their involvement prolonged the civil war and caused collapse of every state institution in DRC.